The De/Construction of Identity: The Complexities of Loss and Separation for Mixed-Race Britain - Rhianna Garrett (Genealogy, 2025)
In the 2017 Danzy Senna novel, New People, the mixed-race protagonist is described as a white ‘passing’ mixed-race woman who interprets the death of her adopted Black mother as a symbol of the death of her Black identity. The book’s themes parallel ongoing multiracial political debates that explore the extent to which mixed-race people with proximity to whiteness perceive individual agency in identity negotiations. This paper examines how mixed-race people in Britain discuss the experience of loss and separation, thereby demonstrating how loss and separation interact with their sense of self. Employing a content and thematic analysis of 19 stories from the British-based organisation Mixedracefaces, my findings show that the mixed-race respondents saw their racially marginalised family members as critical connections to their own. Thus, a process of identity de/construction was instigated when they experienced a loss that perpetuated and/or challenged monoracism. I argue that we must disrupt oppressive monoracial paradigms of ‘race’ that uphold monoracial whiteness and prevent mixed-race identity agency. Through mixed-race counterstories, we can reveal further generational histories of struggles, resistance, love, and refusal in Britain. I intentionally provide a safe space for the millions of mixed people looking for connection through this experience.